(3eQGJY GdZRdGf aj hUa GdZdeGfs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s ((3CMeO Hf eMeO Hf Ydi GdLdGdi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi Ndb GdEfSGf ai CMSf Jbhje abO SCdfi HYV GdENhGf Cf CLeY dg fHPg ai GdMSGf ef GdZdeGf aGeJKdK CeQg GdYGdi s
(3BNQgG (B:s
(3bdJ (B: (3hdh bGd (B: (3dh de Jcf QhVI ddMSf Ch adckG eG cGf LeY ajc GdZUf hGdbeQ dcGf CHdZ ai GdeYfi Je eQGJY GdZRdGf s
(3HgG fXGe GdJYbjHIs
(3hgj fSNI efbhdI ef fSNI fbdJ Yf fSNI GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1650s
Keywords: (3GdSjGSI hGdGLJeGYs